Pengaruh Figur Publik terhadap Persepsi Merek: Studi Kasus Cristiano Ronaldo dan Coca-Cola pada Euro 2020: Penelitian - Bella Safitri Sipayung; Muhammad Raysa; Eka Friska Br Sinaga; Yosi Anjelina Sianturi; Roza Thohiri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the influence of a public figure’s actions—in this case, Cristiano Ronaldo—on Coca‑Cola’s brand perception during Euro 2020. The focal case involves Ronaldo removing two Coca‑Cola bottles from his table at a press conference and recommending mineral water, which triggered public reactions and a temporary decline in Coca‑Cola’s market value. Employing a descriptive qualitative approach and a case study method, data were collected through documentation (press conference recordings, media reports, and social media posts) and a literature review on brand perception theories, celebrity endorsement, and nonverbal communication. Content and semiotic analysis were applied to investigate the symbolism of Ronaldo’s gestures and media narratives in shaping consumer perception constructs. Findings indicate that a simple gesture by a public figure can serve as a powerful signal influencing brand associations and market investment behavior, although long-term effects are moderated by external factors such as global economic trends and corporate communication strategies. These results have implications for marketing practitioners in designing crisis management strategies and leveraging public figures more cautiously, as well as opening avenues for further research on social media dynamics and consumer trust.